Impacts of pH on the Fitness and Immune System of Pacific White Shrimp - Weerathunga, Veran; Huang, Wei-Jen; Dupont, Sam; Hsieh, Hsueh-Han; Piyawardhana, Nathangi; Yuan, Fei-Ling; Liao, Jhe-Syuan; Lai, Chia-Yu; Chen, Wei-Ming; Hung, Chin-Chang (Frontiers in Marine Science, 2021)
The atmospheric partial pressure of CO2 (pCO2) has been increasing dramatically since the beginning of the industrial revolution and about 30% of the CO2 produced by anthropogenic activities was absorbed by the ocean. This led to a perturbation of the seawater carbonate chemistry resulting in a decrease of the average surface ocean pH by 0.1 and termed ocean acidification (OA). Projections suggest that pCO2 may reach 900 μatm by the end of the 21st century lowering the average pH of the surface ocean by 0.4 units. The negative impacts of OA on many species of marine invertebrates such as mollusks, echinoderms, and crustaceans are well documented. However, less attention has been paid to the impacts of low pH on fitness and immune system in crustaceans. Here, we exposed Pacific white shrimps to 3 different pHs (nominal pH 8.0, 7.9 and 7.6) over a 100-days experiment. We found that, even though there were no significant effects on fitness parameters (survival, growth and allometries between length and weight), some immune markers were modified under low pH. A significant decrease in total hemocyte count and phenoloxidase activity was observed in shrimps exposed to pH 7.6 as compared to pH 8.0; and phagocytosis rate significantly decreased with decreasing pH. A significant increase in superoxide production was also observed at pH 7.6 as compared to pH 8.0. All these results suggest that a 100-days exposure to pH 7.6 did not have a direct effect on fitness but lead to a modulation of the immune response.